Biomass and carbon stock estimation of mangrove forests using remote sensing and field investigation- based data on Hai Phong coast - Nguyen, Hai Hoa; An, Le Thanh; Lan, Tran Thi Ngoc; Nghia, Nguyen Huu; Linh, Duong Vo Khanh; Bohm, Simone; Premnath, Charles Finny Sathya (Vietnam Journal of Science and Technology, 2021)
Estimated results of 17 plots evenly distributed across study sites showed that the amount of tree carbon stocks was significantly lower than in soil, normally ranged from 9.9 ÷ 29.55 (tons ha-1) and in contrast by using the Walkley-Black method, these total soil organic carbon were in the range from 81.76 ÷ 323.83 tons ha-1 (average = 161.47±15.85 tons ha-1), which pointed out strong relationship between tree density and soil organic carbon in the study areas.